Vulnerability assessment of drinking groundwater of buchak-kaniv aquifer under the conditions of quality composition long-term transformation - Serhii Levoniuk; Ihor Udalov (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія, 2022)
Problems Statement and Purpose. This article is a continuation of the authors' previous publications on improving the methodical approach to assessing the vulnerability (protection) of drinking groundwater within the Dnipro-Donetsk artesian basin (DDAB) and is a practical component of these studies. In order to find and develop optimal forms of ecological safety management of drinking water supply for the region population, the authors' improved approach to assessing the vulnerability (protection) of drinking groundwater in the strategically important waters of buchak-kaniv aquifer (BKA) was tested.